Answer
36
Step-by-step explanation:
Answer:
5
Step-by-step explanation:
multiplied by ![\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D)
which makes: ![\frac{15}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B15%7D%7B3%7D)
simplify: 5
Answer: Original Price: $5
Step-by-step explanation:
x+0.2x=6
1.2x=6
x=5
Original Price: $5
Answer:
70.925 I believe
Step-by-step explanation:
Answer:
The steps have been shown in the solution below
Step-by-step explanation:
![(3x+1)^{2} - 2(3x+1)=(3x+1)(3x-1)](https://tex.z-dn.net/?f=%283x%2B1%29%5E%7B2%7D%20-%202%283x%2B1%29%3D%283x%2B1%29%283x-1%29)
![9x^{2} +6x+1 -6x-2= (3x+1) (3x-1)\\\\9x^{2} -1=(3x+1)(3x-1)\\\\(3x+1)(3x-1)=(3x+1)(3x-1)\\](https://tex.z-dn.net/?f=9x%5E%7B2%7D%20%2B6x%2B1%20-6x-2%3D%20%283x%2B1%29%20%283x-1%29%5C%5C%5C%5C9x%5E%7B2%7D%20-1%3D%283x%2B1%29%283x-1%29%5C%5C%5C%5C%283x%2B1%29%283x-1%29%3D%283x%2B1%29%283x-1%29%5C%5C)
LHS=RHS Hence, proved.